2019
DOI: 10.1111/wvn.12343
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Data Collected From mHealth Apps to Inform Evidence‐Based Quality Improvement: An Integrative Review

Abstract: Background: The global acceptance and use of technology in health care has resulted in an abundance of mobile health (mHealth) applications (apps) available for use in the delivery and improvement of care. With so many apps available to patients and clinicians, it is important to understand how data from apps are being used to inform quality improvement in practice.Aim: The aim of this integrative review is to establish current knowledge of how mHealth apps are used to produce data to inform quality improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…There has been recent progress in the areas of menstrual health literacy, advocacy, and communication, in part facilitated by the rapid acceptance of mHealth apps, the use of mobile technologies to provide health-related services (tracking information and providing information or education to support an individual's achievement of health objectives). 20,21 At present, there are more than 300 reproductive health mHealth products in the IOS and Google stores, with the majority of the apps focused on women of childbearing age. The apps vary in their depth of pelvic health information, with the majority including cycle and fertility trackers.…”
Section: Progress In Menstrual Health Terminology and Menstrual Hmentioning
confidence: 99%
“…There has been recent progress in the areas of menstrual health literacy, advocacy, and communication, in part facilitated by the rapid acceptance of mHealth apps, the use of mobile technologies to provide health-related services (tracking information and providing information or education to support an individual's achievement of health objectives). 20,21 At present, there are more than 300 reproductive health mHealth products in the IOS and Google stores, with the majority of the apps focused on women of childbearing age. The apps vary in their depth of pelvic health information, with the majority including cycle and fertility trackers.…”
Section: Progress In Menstrual Health Terminology and Menstrual Hmentioning
confidence: 99%
“…Fourteen reviews (systematic or integrative) and metaanalyses were found in this literature review: 10 systematic/integrative, [20][21][22][23][24][25][26][27][28][29] two meta-analyses, 30,31 and two combined. 32,33 Traditional search methods were used with hundreds, if not thousands, of citations first found, with a range of 66 31 to 14,292.…”
Section: Systematic Reviews and Meta-analysesmentioning
confidence: 99%
“…The papers evaluated by the 14 studies ranged from 5 (of 185) 29 to 70 (of 3622). 21 Topics addressed in these papers were cardiovascular disease, 27,29,32,33 cancer, 23,31 chronic disease, 21,25 chronic obstructive pulmonary disease, 30 teledermoscopy, 20 followup after discharge, 28 nurses, 22 apps for quality improvement, 24 and physical activity in elders. 26 A study by Jin et al 32 reported a significant finding, that being telehealth significantly improved cardiovascular risk factors.…”
Section: Systematic Reviews and Meta-analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, a revolution in information technologies has greatly influenced health care practices under the broad definition of digital health. Digital health practices are becoming highly adaptable in both developed and developing countries [1]. Moreover, with the increasing use of smartphones, smart watches, and artificial intelligence-based devices, mobile health (mHealth) is expected to define the standard of health care delivery across the globe.…”
Section: Introductionmentioning
confidence: 99%